Can gallbladder wall thickness by gross examination predicts its carcinoma before histopathological study? - Dr Navyashree N; S. Giriyan, Sujata (Tropical Journal of Pathology and Microbiology, 2019)
Background: The gallbladder lesions are often underappreciated. Though gallbladder carcinomas are less in incidence, it is important to examine all gallbladders on removal so that carcinomas are not missed. In this regard, this study is about predicting the risk of carcinoma gallbladder on gross examination, so that no carcinoma cases are missed and also unnecessary histopathological examination of non-neoplastic conditions which forms the major bulk of gallbladder pathology can be avoided. Objectives: 1) To study gross and microscopic features of gallbladder in cholecystectomy specimens. 2) To study association of gross features and carcinoma of gallbladder. Methods: 4 years study was conducted on 316 specimens of cholecystectomy in KIMS, Hubballi from June 2014 to May 2018. Gallbladder specimens were processed by standard procedures and histopathological patterns were studied. Results: The present study included patients from 7 to 87 years of age with Male: Female ratio 1:1.8 and majority were in 5th and 7th decade. Chronic cholecystitis (78.6%) was most common gallbladder lesion. Incidence of gallbladder carcinoma was 1.89% and majority were in 7th decade. Statistically significant association was found between carcinoma and increased thickness of gallbladder wall.